Forage corn production with two irrigation systems and three levels of applied evaporation - Gutiérrez-Guzmán, Ulises Noel; Ríos-Vega, María Esther; Núñez-Hernández, Gregorio; Esquivel-Romo, Amaury; Vázquez-Navarro, José Manuel; Anaya-Salgado, Antonio (Revista Mexicana de Ciencias Agrícolas, 2022)
The efficiency in the use of water to produce forage groups a series of components related to the crop and the irrigation system, which consists of obtaining a greater production per unit of water consumed. The objective of the work was to know the yield, nutritional quality and water use efficiency (WUE) of the forage corn (Zea mays L.) culture in two irrigation systems under three levels of applied evaporation. The work was established on April 19, 2019, at the La Laguna Experimental Field (CELALA) of the National Institute of Forestry, Agricultural and Livestock Research (INIFAP), located in Matamoros, Coahuila, Mexico. The irrigation systems evaluated were: subsurface drip and surface irrigation. In both systems, the applied sheets corresponded to 100, 75 and 50% of free evaporation of the class ‘A’ evaporimeter pan. The harvest was carried out when the grain was in the R3 milky grain stage. The experimental design used was split plots with four repetitions. The interaction of subsurface drip irrigation system -100% evaporation was higher (p< 0.05) in the variables of height with 2.05 m, green forage yield with 55.08 t and dry forage yield 14.85 t. The combination with the best behavior in WUE in yield with 1.98 kg m-3 and the highest values in WUE in forage quality was surface irrigation system -75% evaporation. There were significant differences between irrigation systems in the quality variables with better results in the surface irrigation system.